There May Be a Way to Say 'NO' to Gastric Injury Associated with the Combined Use of Aspirin and Cyclooxygenase-2 Inhibitors - Jennifer J Williams; Paul L Beck (Canadian Journal of Gastroenterology)
Due to evidence that it reduces the frequency of cardiac events and stroke, the use of daily low-dose aspirin has dramatically increased over the past 20 years (1). The use of other nonsteroidal anti-inflammatory drugs (NSAIDs) for the relief of pain and inflammation has also increased (2). Unfortunately, aspirin and conventional NSAIDs such as diclofenac are notorious for causing significant damage to the upper gastrointestinal tract because they suppress prostaglandin (PG) synthesis (3).